Dealing with journal review results: How successful and productive authors avoid and respond to manuscript rejections - Safnil Arsyad; Muhammad Zaim; Juliana Othman (EduLite: Journal of English Education, Literature and Culture, 2026)
Both early-career writers and authors with more experience may get rejected when they submit a manuscript to a distinguished or high impact journal; however, different authors may respond to rejections differently and this will determine whether or not an author is successful and publish a lot of articles in good journals. This study is aimed at investigating how productive authors react to article rejections they obtain from journal editors. This study used a qualitative approach and inductive coding data analysis techniques and processes were used to examine the data from semi-structured interview. Ten productive authors in the field of education from Malaysia and Indonesia were interviewed using a semi-structured interview to get the data. The results show that: 1) when responding to a rejection, most authors revised their manuscripts following editor or reviewers’ comments and corrections before submitting it to another journal with a lower ranking or Quartile value, 2) the major factor causing a rejection according to the respondents is a manuscript which is very similar or a duplicate of an already published one, and 3) the major factor causing a rejection according to the respondents is a manuscript which is very similar or a duplicate of an already published one.. Thus, productive authors keep writing although their manuscripts often got rejected by journals because authors learn from comments and corrections from editors and/or reviewers. Novice authors should not give up writing and revising their manuscripts although they often experience rejections from journals’ reviewers and/or editors.